2011
DOI: 10.1007/s00484-011-0432-7
|View full text |Cite
|
Sign up to set email alerts
|

Misting and fan cooling of the rest area in a dairy barn

Abstract: This summer study aimed to evaluate the effect on dairy cows, kept in a free stall barn equipped with fans and sprinklers in the feeding area, of the delivery rate of misters in a cooling system in rest areas with different bedding materials. Thirty cows were divided into two homogenous groups according to milk yield and kept in two pens: one had beds with sand (SAMM) while the other had straw (STLM). Each pen was equipped with 2 fans (Ø 70 cm, 0.50 kW) and 2 misters (delivery rate of 11.2 and 22.5 L/h in STLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…The cows that rested from 14.6 to 16.4 h of daytime had a milk production from 32.8 to 33.7 kg day -1 . Several authors report the benefit of lying time correspond to cow comfort, health, and level of milk production and suggest about 14 h day -1 as optimal duration (Calegari et al, 2012). From these preliminary results, the behaviour of standing in the cubicles seems inversely correlated to milk production (Belle et al, 2012).…”
Section: Resultsmentioning
confidence: 67%
“…The cows that rested from 14.6 to 16.4 h of daytime had a milk production from 32.8 to 33.7 kg day -1 . Several authors report the benefit of lying time correspond to cow comfort, health, and level of milk production and suggest about 14 h day -1 as optimal duration (Calegari et al, 2012). From these preliminary results, the behaviour of standing in the cubicles seems inversely correlated to milk production (Belle et al, 2012).…”
Section: Resultsmentioning
confidence: 67%
“…Several authors report the benefit of lying time on the cow comfort, health and production and suggest about 14 h/day as optimal duration (Calegari et al, 2012). Consequently, the extension of the lying activity obtained with a different timing of the cooling system could improve the well being of the cows and, therefore, their production and health.…”
Section: Articlementioning
confidence: 99%
“…Another study focused on the comparison among different kind of cooling systems and analysed the differences in thermoregulatory responses of cows, but without any analysis of the behaviour (CorreaCalderon et al, 2004). Further two studies on the efficacy of different cooling systems included cow behaviour analysis and were carried out in free-stall dairy houses with direct access to a large unshaded hard court paddock (Frazzi et al, 2000;Calegari et al, 2012). Specifically, the last one was carried out in a free-stall dairy house equipped with two different kind of cooling systems installed in the feeding alley and in the resting area, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Honig et al (2012) found that increasing the cooling frequency of high-yielding dairy cows from 5 to 8 sessions a day, improves their performances and welfare. Calegari et al (2012) found that also with the presence of the sprinkler systems installed above the feeding alley, cows suffered a mild-moderate heat stress which was more emphasised in the pen equipped with straw bedded stalls.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the cooling system was proven to be effective in reducing cow heat stress. Analogous studies in zones characterised by hot-humid climate, such as those of the Mediterranean basin, are rather less frequent (Honig et al, 2012;Calegari et al, 2012) and the real benefits of this type of cooling system on cow welfare should be object of further researches, because their efficacy could be negatively affected by high levels of relative humidity. Honig et al (2012) found that increasing the cooling frequency of high-yielding dairy cows from 5 to 8 sessions a day, improves their performances and welfare.…”
Section: Introductionmentioning
confidence: 99%